Pelatihan Tips dan Trik Penyelesaian Soal TOEFL bagi Himpunan Mahasiswa Ekonomi Syariah Universitas Trunojoyo Madura - Pujiati, Tri; Rosyadi ZA, Dede; Musadad, Ahmad; Nahidloh, Shofiyun; Prasetya, Rizky Eka (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Test of English as a Foreign Language (TOEFL) is a mandatory English proficiency test for university students as a measure of foreign language proficiency. However, a common problem is students’ unpreparedness for the test due to a lack of understanding of tips and tricks for answering TOEFL questions correctly. This community service activity was designed using a Participatory Action Research (PAR) approach. The purpose of this community service activity was to provide tips and tricks for answering TOEFL questions to the Islamic Economics student association at the Faculty of Islamic Studies, Trunojoyo University. A total of 50 participants participated in this community service activity. This community service activity was designed using a training method that focused on the problems faced by the participants regarding TOEFL test-solving strategies, so that they would be better prepared when taking the test at a language center or TOEFL test provider. This community service activity focused on three stages: preparation; training; and evaluation. The results of this community service activity had a positive impact on literacy skills related to TOEFL question-solving strategies. The results of the questionnaire given showed that students had a good understanding of the strategies and methods for solving TOEFL test questions so that they were better prepared to face TOEFL questions when they took the TOEFL test.